2005
DOI: 10.1086/432904
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Collapse in the Cosmic Web

Abstract: We study the kinematics of the gaseous cosmic web at high redshift using Ly forest absorption in multiple QSO sight lines. Observations of the projected velocity shifts between Ly absorbers common to the lines of sight to a gravitationally lensed QSO and three more widely separated QSO pairs are used to directly measure the expansion of the cosmic web in units of the Hubble velocity, as a function of redshift and spatial scale. The lines of sight used span a redshift range from about 2 to 4.5 and represent tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 95 publications
4
43
0
Order By: Relevance
“…Its spectrum shows absorption features at the wavelengths expected for the Bridge gas (Smoker et al 2005). This also applies to direct evidence that things have moved apart from each other with time, deduced from statistics of the Ly α forest between z = 2 and 4.5 (Rauch et al 2005). …”
Section: Distance Indicators and Gravitational Lensingsupporting
confidence: 58%
“…Its spectrum shows absorption features at the wavelengths expected for the Bridge gas (Smoker et al 2005). This also applies to direct evidence that things have moved apart from each other with time, deduced from statistics of the Ly α forest between z = 2 and 4.5 (Rauch et al 2005). …”
Section: Distance Indicators and Gravitational Lensingsupporting
confidence: 58%
“…This range was chosen on the basis of several observational findings. Studies of close QSO pairs have found a strong C iv clustering signal within ∼ 200 km s −1 , which might indicate the outflow velocity could be less than ∼ 200 km s −1 (Rauch et al 2005). A significant clustering signal of H i is also found at a transverse velocity separation at ∼ 500 km s et al 2006).…”
Section: Systemsmentioning
confidence: 96%
“… e Rauch et al (2005), using VLT spectra, found ‘all of the systems’ are in common apart from differences in column densities. …”
Section: Absorber Size As a Function Of Nh Imentioning
confidence: 99%